New Fixed Point Results for Fractal Generation in Jungck Noor Orbit with s-Convexity - Shin Min Kang; Waqas Nazeer; Muhmmad Tanveer; Abdul Aziz Shahid (Journal of Function Spaces)
We establish new fixed point results in the generation of fractals (Julia sets, Mandelbrot sets, and Tricorns and Multicorns for linear or nonlinear dynamics) by using Jungck Noor iteration with s-convexity.